PENGARUH MOTIVASI KERJA, EMPLOYEE ENGAGEMENT DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN DINAS PERDAGANGAN DAN PERINDUSTRIAN KOTA DEPOK - Silvia Nur Azizah (2021)
The Department of Trade and Industry of Depok City is experiencing problems with employee satisfaction. Therefore, this study aims to determine partially and simultaneously the variables used on employee job satisfaction. The sample used in this study were employees of the Department of Trade and Industry of Depok City where the researcher used a saturated sample that employed 70 employees. This data processing results in: 1) job satisfaction is influenced by work motivation by the employees themselves, 2) job satisfaction is also influenced by employee engagement, 3) employee job satisfaction is determined by the compensation provided by the company to employees, and 4) the three variables are Simultaneous influence on employee job satisfaction.